2009
DOI: 10.1037/a0015211
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of marriage and relationship education on couples' communication skills: A meta-analytic study.

Abstract: This meta-analysis probes into previous research substantiating the positive effects of marriage and relationship education (MRE) on couples' communication skills. We reviewed 97 MRE research reports that yielded 143 distinct evaluation studies. We found modest evidence that MRE functions both as a universal prevention and as a selective or indicated prevention. That is, MRE demonstrates program effects at longer term follow-ups for well-functioning couples and at postassessment and shorter term follow-ups for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
182
1
13

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(207 citation statements)
references
References 76 publications
11
182
1
13
Order By: Relevance
“…1-1) Communication Skills: Communication skills are of the types that when the spouses learn, they can improve their relationships (4). Training Communication skill aims to help the couples to form and boost their marital health and stability and relationships (17). It's suggested that the best solution to raise marital contentment in couples is to use social norms, satisfaction with the relationships and flexibility in their desires (18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1-1) Communication Skills: Communication skills are of the types that when the spouses learn, they can improve their relationships (4). Training Communication skill aims to help the couples to form and boost their marital health and stability and relationships (17). It's suggested that the best solution to raise marital contentment in couples is to use social norms, satisfaction with the relationships and flexibility in their desires (18).…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have indicated that the capabilities an individual acquires in these trainings enable him/her to value life opportunities and get prepared to cope with probable dangers (14)(15)(16)(17)(18). Also training life skill raises mental and social capabilities and helps the person to face life situations effectively and to adaptively function with other humans, society, culture and the environment and provide their mental health.…”
Section: Resultsmentioning
confidence: 99%
“…Uno de ellos, incluyó 26 estudios de cursos de educación premarital, evaluados con diseños experimentales, cuasi experimentales, no experimentales y ex-post-facto, donde se encontró que los programas en general son efectivos con un tamaño del efecto de .80 (Carroll et al, 2003). Otros meta análisis realizados en educación para parejas, evidencian un tamaño del efecto moderado a alto en incrementar la comunicación en la pareja (Blanchard, Hawkins, Baldwin, y Fawcett, 2009) y un tamaño del efecto pequeño a moderado en la satisfacción con la relación, evaluada inmediatamente después de finalizada la intervención (Carroll et al, 2003;Hawkins et al, 2008). Un tercer meta análisis realizado por Hawkins, Blanchard, Baldwin y Fawcett (2008) consideró, 117 estudios que incluían intervenciones educativas de diverso tipo: educación para las relaciones impartida para personas solteras, para parejas seriamente comprometidas, Diana RiveRa, PatRicio cumsille, caRmen Domínguez y caRmen gloRia HiDalgo programas de promoción dirigidos a novios y matrimonios, y otros para parejas en vías de ser padres.…”
Section: La Efectividad De Los Programas De Prevenciónunclassified
“…Esse foco tem sido considerado em intervenções em educação para relacionamento de casal, largamente praticadas mundo afora, sobretudo com casais adultos (Halford et al, 2008;Blanchard et al, 2009). Estas tem sido focadas no desenvolvimento de conhecimento, atitudes e habilidades de comunicação e manejo de conflito para relacionamentos amorosos satisfató-rios.…”
Section: Características De Relacionamentos De Namoro Saudáveisunclassified